Functional expression of a Mo-dependent formate dehydrogenase in Escherichia coli under aerobic conditions - Marion Schulz; Anne Berger; David Roche; Emilie Pateau; Ivan Dubois; Valérie A. Delmas; Mélodie Cadillon; Madeleine Bouzon; Volker Döring (PLoS ONE, 2025)
Background Oxygen tolerant complex metal-dependent formate dehydrogenases hold potential for biotechnological applications. Principal Findings In this work, we report the functional expression of the complex, molybdenum-dependent soluble formate dehydrogenase encoded by the fdsGBACD operon from Cupriavidus necator (CnFDH) in Escherichia coli. Expression of the operon from plasmids or from a copy integrated in the chromosome enabled growth of an energy-auxotrophic selection strain on formate as sole energy source under aerobic conditions. Growth could be accelerated in turbidostat, leading to a drop of the generation time of 1 hour. While no mutation was found in the operon of evolved isolates, genome sequencing revealed non-synonymous point mutations in the gene focA coding for a bidirectional formate transporter carried in all isolates sequenced. Reverting the mutations led to a drop in the growth rate demonstrating the focA gene as principal target of continuous culture adaptation. Significance A member of the oxygen-tolerant subclass of complex FDH showed stable formate oxidation activity when expressed in the heterologous host E. coli , a model organism of biotechnology. The integration of the operon in the chromosome offers the possibility of structure/function studies and activity enhancements through in vivo mutagenesis, which can also be applied to CO 2 reduction in appropriate selection hosts.